STATE CONTROL MECHANISMS OF THE REGION INDUSTRIAL ENTERPRISES BUSINESS PROCESSES ECOLOGIZATION - Andrey E. SAFRONOV (Advanced Engineering Research, 2010)
Mechanism of the regional control of the industrial enterprises business processes ecologization under transformation conditions. Methods of environmental economics developed by both Russian and foreign scientists are examined.